The Role of Sex-Related Alcohol Expectancies in Alcohol-Involved Consensual and Nonconsensual Sex Among Women of Asian/Pacific Islander and Women of European Race/Ethnicity. Issue 7 (2nd September 2018) - Dir, Allyson L.; Andrews, Arthur R.; Wilson, Sarah M.; Davidson, Tatiana M.; Gilmore, Amanda K.
Abstract : Alcohol-involved sexual experiences, including incapacitated sexual assault and alcohol-involved sex, are major public health concerns among college women. Further, racial/ethnic diversity among college students is increasing, particularly with regard to increases in college students of Asian/Pacific Islander (API) race/ethnicity. Of relevance, evidence suggests differences in sexual assault rates across ethnicities and cultures; however, no known study to date has examined differences by ethnicity and first language in expectancies and experiences specifically surrounding alcohol and sex. The current study sought to examine differences in incapacitated sexual assault, alcohol-involved sex, and heavy episodic drinking, as well as differences in sex-related alcohol expectancies among native English-speaking college women of European (EU) race/ethnicity, native English-speaking women of API race/ethnicity, and non–native English-speaking women of API race/ethnicity (NNES-API). EU reported higher frequency of heavy episodic drinking, alcohol-involved sex, and incapacitated sexual assault compared to API and NNES-API. In addition, API reported more frequent alcohol-involved sex and incapacitated sexual assault compared to NNES-API, in part due to API's stronger endorsement of sexual disinhibition–related alcohol expectancies (indirect effects: β = −.04, p = .04, and β = −.07, p = .04, respectively). Findings highlight the important role of expectancies in acculturation and influence on actual alcohol-involved sex and sexual assault.